RETHINKING LIS AND ARCHIVAL EDUCATION AND PRACTICE IN THE PHILIPPINES: TAKING ON SOCIAL MEMORY AS A PARADIGM - Buenrostro, Iyra S. (Journal of Philippine Librarianship; Vol 35 (2015), 2016)
This article discusses the concept of social memory as a paradigm for the LIS and archival education and practice in the Philippines. The author argues that the close partnership between LIS and Archival Studies in the Philippines and the shift of functions from storage to access call for a “shared” paradigm, which is at the same time socially and culturally-sensitive. It is also explored in this essay the potential of the partnership or convergence between LIS and Archival Studies in the mediation of social memory, along with the ascribed responsibility and authority to archives and libraries in rendering access and information services. In this paradigm, both the librarians and archivists are brought into a position where they possess an understated power in collecting, establishing and propagating social memory.
Keywords: archival education, social memory, library and information science education, libraries, archives